2016
DOI: 10.1093/ejcts/ezw167
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up after aortic root replacement with the Shelhigh® biological valved conduit: a word of caution!

Abstract: The first long-term follow-up after aortic root replacement with the Shelhigh® BioConduit revealed a relatively high rate of death and very high rate of reoperations due to endocarditis, aorto-ventricular disconnection and structural valve failure. This may be potentially connected to the nature of the implanted valved conduit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…They reported an unexpectedly high rate of death along with an elevated number of reoperations (8.6%) during the midterm follow‐up, mostly due to endocarditis and aorto‐ventricular disconnection or false aneurysm formation of the conduit 15 . Similar results were reported 1 year later by Sahin et al, 16 analyzing a cohort of 63 patients implanted with the same conduit at a median follow‐up of 9.5 years. They reported a surprisingly high rate of prosthesis‐related deaths (6.4%), endocarditis (17%) and reoperations (16%), and advised against the use of the Shelhigh conduit.…”
Section: Discussionsupporting
confidence: 64%
“…They reported an unexpectedly high rate of death along with an elevated number of reoperations (8.6%) during the midterm follow‐up, mostly due to endocarditis and aorto‐ventricular disconnection or false aneurysm formation of the conduit 15 . Similar results were reported 1 year later by Sahin et al, 16 analyzing a cohort of 63 patients implanted with the same conduit at a median follow‐up of 9.5 years. They reported a surprisingly high rate of prosthesis‐related deaths (6.4%), endocarditis (17%) and reoperations (16%), and advised against the use of the Shelhigh conduit.…”
Section: Discussionsupporting
confidence: 64%
“…Studies have reported cases of degradation or stenosis of No-React products used cardiac and thoracic surgery. [12][13][14] In contrast, other centers with even larger patient cohorts have not reported such issues. 15,16 Because of our aforementioned case and the reported data, we have implemented a more rigorous follow-up.…”
Section: Discussionmentioning
confidence: 95%
“…Perhaps the sterile abscess formation was suggested to be due to an immunogenic reaction to the xenograft manifested as xenogeneic complement-mediated graft rejection. 19,20 Furthermore, early failure of the Shelhigh pulmonary valve conduit used for right-sided reconstruction in infants was reported by Pearl et al and was explained to be due to foreign body reaction leading to pseudointimal peel formation and subsequent early conduit stenosis. 21…”
Section: Commentsmentioning
confidence: 99%